Effect of ZrO2 content on the microstructure and flexural strength of Al2O3-ZrO2 composites with the stored failure energy-fragmentation relations - Yildiz, Betul Kafkaslioglu; Tur, Yahya Kemal (Elsevier Sci Ltd, 2021)
High flexural strength is an important mechanical property for a ceramic armor component to withstand high tensile stresses and protect its structural integrity against multiple hits. Also, larger fragments are required in fragmentation as larger fractured parts are harder to leave of the way for the penetrator and cause more abrasion and higher penetration resistance. In this study, the effect of different ZrO2 content (0, 0.5, 1, 3, 5, 10, 20 vol%) on the flexural strength of Al2O3-ZrO2 composites was investigated with relationship of the stored failure energy-crack length to evaluate the fragmentation behavior under possible impact conditions. Monotonic equibiaxial flexural strength test was used to measure the fracture strength. The highest strength was obtained for 20 vol% ZrO2 containing composite as 435 +/- 78 MPa, similar to 24% increase in comparison with the pure Al2O3. The transformation of tetragonal to monoclinic phase occurred during the strength test in the 10 and 20 vol% ZrO2 content composites. 20 vol% ZrO2 containing composite had the smallest total crack length accompanying the largest fragment size for a given fracture energy among all the composites due to the stress-induced transformation of ZrO2 consumes energy that results in decreasing effective crack driving energy required for the crack branching.
Keywords: Alumina; Zirconia; Flexural strength; Failure energy